2022
DOI: 10.3389/fmicb.2022.800604
|View full text |Cite
|
Sign up to set email alerts
|

Disordered Gut Microbiota Correlates With Altered Fecal Bile Acid Metabolism and Post-cholecystectomy Diarrhea

Abstract: Post-cholecystectomy diarrhea (PCD) is a common complication of gallbladder removal, and gut microbiota changes have been determined in PCD patients. Bile acid diarrhea (BAD) is supposed to be the main pathogenic factor for PCD due to the disrupted fecal bile acid metabolism in diarrheal patients. However, the profiling of bile acid metabolite alteration in PCD is unclear and whether changed gut microbiota and fecal bile acid metabolism are correlated is also underdetermined. The fecal bile acid metabolites fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…Frontiers in Microbiology 07 frontiersin.org for bacterial growth both directly (antimicrobial) and indirectly (diarrhoea). We are, however, unable to account for why reduced diversity was not seen in equal measure in the post-cholecystectomy and Crohn's disease cohorts despite a recent study demonstrating reduced diversity in the post-cholecystectomy cohort compared to non-post-cholecystectomy patients and healthy controls (Xu et al, 2022). Further research is needed to explore the relationship between bile acids, bile acid receptors such as the farnesoid X receptor (FXR) and FGF-19 and their interaction with the microbiome to understand the pathophysiology of disease underpinning these different cohorts.…”
Section: Discussionmentioning
confidence: 83%
“…Frontiers in Microbiology 07 frontiersin.org for bacterial growth both directly (antimicrobial) and indirectly (diarrhoea). We are, however, unable to account for why reduced diversity was not seen in equal measure in the post-cholecystectomy and Crohn's disease cohorts despite a recent study demonstrating reduced diversity in the post-cholecystectomy cohort compared to non-post-cholecystectomy patients and healthy controls (Xu et al, 2022). Further research is needed to explore the relationship between bile acids, bile acid receptors such as the farnesoid X receptor (FXR) and FGF-19 and their interaction with the microbiome to understand the pathophysiology of disease underpinning these different cohorts.…”
Section: Discussionmentioning
confidence: 83%
“…We found similar ora richness and structure in both groups. However, Xu et al [27]found that the abundance and homogeneity of intestinal ora were signi cantly lower in DG group compared with NG group, as well as a signi cant difference in the composition of intestinal ora, which may be related to the elevated secondary bile acids concentration after cholecystectomy. The accumulation of secondary bile acids in colon stimulates colonic 5-HT and increases colon motility, leading to diarrhea [28].…”
Section: Discussionmentioning
confidence: 98%
“…High expression of Muribaculum has been suggested as a possible marker of bile acid metabolism disorders (Marion et al, 2020). Erysipelotrichaceae UCG-003 has been reported to be associated with disorders of bile acid metabolism as well as intestinal dysfunction (Xu et al, 2022), which is also related to the induction of intestinal inflammation (Cheng et al, 2021) and tumor development (Zhao et al, 2021). Sutterella has been mentioned more in Crohn's disease and inflammatory bowel diseases in recent years.…”
Section: Discussionmentioning
confidence: 99%